Nematodos asociados a plantones de frutales y citricos en viveros comerciales - Verdejo, S.=700 1 Pinochet, J.
(Es, En)
ilus., 25 ref.
Keywords: DISTRIBUCION GEOGRAFICA; NEMATODA; MELOIDOGYNE; PRATYLENCHUS; TYLENCHORHYNCHUS; TYLENCHUS; METODOS DE CULTIVO; ESPAÑA